PENGARUH NORMAL FLORA Streptococcus sp. KARANG GIGI TERHADAP PEMERIKSAAN DARAH LENGKAP PADA MAHASISWA UNIVERSITAS NAHDLATUL ULAMA SURABAYA - Rahayu Anggraini; Umi Hanik; Gilang Nugraha; Dwi Lestari Pertiwi (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2017)
This study aims at determining the normal flora of Streptococcus sp., the inhabitants of the oral cavity in the tartar that can lead to health problems. This study is an observational study with cross sectional analytic approach performed on 47 samples of dental smear for Streptococcus sp. bacteria identification and EDTA blood samples for Hemoglobin level examination, hematocrit percent, the number of erythrocytes, leukocytes and platelets in University of Nahdlatul Ulama Surabaya students. The result of Independent Samples T Test data analysis in a cut point showed that the levels of hemoglobin, number of leukocytes and platelets look significantly different with p <0.05in individuals with normal flora Streptococcus alpha and Streptococcus gamma. The conclusion in this study, in individuals with normal flora Streptococcus alpha, can decrease hemoglobin level, whereas in individuals with normal flora Streptococcus gamma can increase the number of leukocytes and decrease the number of platelets.